2017
DOI: 10.5530/ijper.51.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Heat-Treated Cucumber (Cucumis sativus L.) Juice Against Lead-Induced Detoxification in Rat Model

Abstract: Background: In recent years, the development of efficient green chemistry approaches for detoxification of heavy metal such as lead (Pb) poisoning has become a major focus of researchers. Objectives: This study was aimed to evaluate the effectiveness of heattreated cucumber juice on the protection of Pb-induced acute liver and kidney damages. Methods: Initially, during detoxification of lead, lead acetate (200 ppm dissolved in distilled water) was given to rats in drinking water for 5 weeks. Cucumber juice was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Tomato and cucumber samples showed an increase in the activity of ALDH (41.19% and 87.25%). Investigators have reported that heat treated cucumber had the ability to enhance the activity of ALDH and ADH ( Bajpai et al., 2016 ). Contrary to this result, our work showed a significant decrease of ADH activity by cucumber.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato and cucumber samples showed an increase in the activity of ALDH (41.19% and 87.25%). Investigators have reported that heat treated cucumber had the ability to enhance the activity of ALDH and ADH ( Bajpai et al., 2016 ). Contrary to this result, our work showed a significant decrease of ADH activity by cucumber.…”
Section: Resultsmentioning
confidence: 99%
“…Several natural compounds like 6-gingerol ( Takahashi et al., 2010 ), dehydroevodiamine ( Wang et al., 2016a ), ginsenosides ( Kim et al., 2011 ), linolenic acids ( Lee et al., 2014a ) among many others, have been recommended as a cure for hangover. Researchers have investigated and identified natural components (such as polyphenols) from various food sources such as fruits, mushroom, and herbs to alleviate hangover symptoms ( Zhao et al., 2017 , Zhang et al., 2016 , Kim, 2016 , Bajpai et al., 2016 ). These natural food sources are reported to function effectively by exhibiting positive effects on the hepatic enzymes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Cucumber juice may cause sulfur-containing molecules to form ionic interactions with lead nitrate during the chelation process. Additionally, CS has anti-oxidant properties that contribute to its protective properties (46).…”
Section: Cucumis Sativusmentioning
confidence: 99%
“…An investigation by Lee, Song, Kim, Joo, Park, Jeon, Shin, Park, Lee, Ly, Kim, Lee and Kim [14] of the effects of a preparation of combined glutathione-enriched yeast (GEY) and rice embryo/soybean (RES) extracts (20:1), GEY/RES, on experimentally induced ethanol hangover in male Sprague-Dawley rats found that GEY/RES reduced the blood concentrations of alcohol and acetaldehyde by modulating alcohol-metabolizing enzymes and by exhibiting antioxidant activity, suggesting that it might be a promising candidate for improving an alcoholic hangover. Bajpai, et al [20] reported that heat-treated cucumber juice detoxified alcohol in experimental rats. A human study by Mammen, et al [21] found that clove bud polyphenols alleviated changes in inflammation and oxidative stress biomarkers…”
Section: Related Studiesmentioning
confidence: 99%